Gender-Based Risk and Protective Factors for Psychological Distress in the Midterm Recovery Period Following the Great East Japan Earthquake. (28th August 2018) - Ishiguro, Aya; Inoue, Machiko; Fisher, Jane; Inoue, Mariko; Matsumoto, Shoko; Yamaoka, Kazue
ABSTRACT: Objectives: Women and men might experience psychological distress differently during a disaster. This study investigated gender differences in the factors associated with psychological distress among working-age people 1 to 2 years after the Great East Japan Earthquake. Methods: A cross-sectional household survey of victims who remained living in their homes was conducted between May and December 2012 in Ishinomaki City, Japan. Psychological distress was defined as a Kessler Psychological Distress Scale ≥5, and gender differences were examined using a logistic regression analysis. Results: Data were obtained from 2593 individuals, and 1537 participants were included in the analyses. Psychological distress was observed in 28.0% of the participants. Living in a household without a salaried income and a low frequency of leaving the house were associated with psychological distress among women. Young age, lack of occupation and no informational support were associated with psychological distress among men. Income change due to the disaster and health complaints were associated with psychological distress in both genders. Conclusions: For women, stable household income and frequently leaving the house can be protective factors. For men, intervention focusing on young people, occupational support, and informational support may be useful. Income change after the disaster and health complaints may be risk factors in both genders. ( Disaster Med Public Health Preparedness . 2019;13:487-496)